The effect of stimulus context on change blindness - Modić Stanke, Koraljka; Tonković, Mirjana psihologinja; Vranić, Andrea (2010)
An apparent failure in detecting a change in the observed scene during a visual disruption is termed change blindness. Research has shown the importance of top-down (expectations, knowledge) and bottom-up (color, size) processes in the occurrence of this phenomenon. The aim of this research was to examine the effect of the disruption of stimulus context on the speed of change detection. Using photographs, we assumed that the change detection will be slower if the changed detail is contextually different from the rest of the photo. Furthermore, we wanted to examine a possible effect of spatial location of change on the detection time. A 2x2x2 within-subject design was used. The independent variables were: 1) type of the photograph (color vs. b/w), 2) color of the changed detail (color vs. b/w), and 3) spatial location of the change (left/right). All participants (N=51) were right-handed. In a flicker paradigm a following flicker sequence was used in a loop: an original picture (250ms), empty screen (200ms), a picture with a changed detail (250ms), empty screen (200ms). Participants were instructed to stop the sequence as soon they detect a change. The results show the interaction of the color of the changed detail and the type of photograph, and this interaction shows that disappearance of b/w detail is detected faster if its context is a colored one, rather than a b/w one. The opposite goes for the colored detail – the change is detected faster when the detail is changed within b/w context. A significant interaction of the color of the detail and the spatial position of the change was also found. The advantage of detecting colored detail over b/w detail was found when change occurred on the right side of the screen. No such advantage was found for the left side of the screen. These results implicate the importance of context for change blindness and imply the need for further research on picture and detail characteristics for better understanding of the change blindness phenomenon.
Projekt MZOS
Projekt MZOS
ENG